The forgetfulness of the aromatic time and contemplation as emancipatory praxis: some reflections from reading Byung-Chul Han (2020)
The article reflects on Byung-Chul Han’s work and his invitation to understand time from a different conception. It also describes the practice of hsiang yin (aroma seal) used in China until the 19th century and explains how this tradition influenced the way ancient Chinese understood time and its interaction with space. Based on this reflection, there is an analysis of how "time transforms space" and a discussion about the benefits modern societies could perceive from going back to this traditional form of interacting with time.